Contributions to the Eocene palaeontology and stratigraphy of Beira Alta, Portugal II - New Late Eocene mammalian remnants from Coja (Portugal) and the presence of Palaeotherium magnum Cuvier - Antunes, M. Telles (2010)
The presence of Palaeotherium magnum in the fauna from Coja is recorded. It is well in agreement with the earlier reporting to the Montmartre level from the Ludian stage. Field data as well as compatibility with the remaining taxa and the identical fossilization of all the specimens indicate that all the vertebrate fossils come from the same horizon in the lithostratigraphic unit "Arcoses de Côja".